Fault diagnostic algorithm for precut farctionation column - 203119 Heng, Han Yam; Mohamad Wijayanuddin Ali; Mohd. Zaki Kamsah; Symposium of Malaysian Chemical Engineers (17th : 2004 : Perak) (Skudai : Universiti Teknologi Malaysia, 2004)
53